Thrombolytic activity of Coriandrum sativum - Shahriar, Mohammad; Islam, Md Siddiqul; Islam, SM Ashraful; Parvin, Salma; Afrin, Nazia (Journal of Bangladesh Academy of Sciences, 2014)
The leaves of Coriandrum sativum were subjected to thrombolytic activities. The thrombolytic activities were assessed by using human blood samples and the results were compared with standard streptokinase (SK). In this study, the methanol soluble fraction (MSF) exhibited highest percentage of thrombolytic activity (60.12 ± 1.91). However, significant thrombolytic activity was demonstrated by the crude ethanol extract (CEE) and n-hexane soluble fraction (HSF) of C. sativum (45.85 ± 0.69) and (22.22 ± 1.42), respectively. DOI: http://dx.doi.org/10.3329/jbas.v37i2.17567 Journal of Bangladesh Academy of Scnces, Vol. 37, No. 2, 245-247, 2013